The effects of hot rolling process on mechanical properties, corrosion resistance, and microstructures of Mo-Ni alloyed steels produced by powder metallurgy - Elkilani Rajab Hussein Rajab; Çuğ Harun; Erden Mehmet Akif (Science of Sintering)
This study examined the effects of hot rolling on the microstructure, tensile strength, and corrosion behaviors of three different alloy steels made by powder metallurgy: Fe-0.55C, Fe-0.55C-3Mo, and Fe-0.55C-3Mo-10Ni. 700 MPa pressure was applied to press the particles. The cold pressed samples were sintered in a mixed-gas atmosphere (90% nitrogen, 10% hydrogen) at 5°C/min up to 1400°C for 2 hours. Then, the produced steels were hot rolled with a deformation rate of 80%. The microstructures show that deformed Mo and Mo- Ni steels have finer microstructures, better mechanical properties than undeformed Mo and Mo-Ni steels, and MoC, MoN, or MoC(N) was formed in the Mo-Ni steels. The highest mechanical properties were obtained in rolled steel samples containing Mo-Ni, followed by rolled Mo steel and rolled carbon steel samples, and then unrolled samples. Additionally, Tafel curve analysis demonstrated that alloy corrosion resistance rose as Ni concentration increased. It has also been observed that the hot rolling process improves corrosion resistance. The increase in the density value with the rolling process emerged as the best supporter of corrosion resistance.